Coordination and motor function associated with mental madurity in children aged from 4 to 8 years - Robles Mori, Herbert (2008)
A total of 90 children (boys and girls) from a Psychological Center in Lima were subjected o a correlational study, where the research questions was: Are coordination  and motor function related to mental maturity in children (boys and girls) aged from 4 to 8 years?